2014
DOI: 10.1371/journal.pone.0106571
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Bcl-2 Inhibitor Obatoclax Delays Cell Cycle Progression and Blocks Migration of Colorectal Cancer Cells

Abstract: Despite the fact that new treatment regimes have improved overall survival of patients challenged by colorectal cancer (CRC), prognosis in the metastatic situation is still restricted. The Bcl-2 family of proteins has been identified as promising anti cancer drug target. Even though small molecules targeting Bcl-2 proteins are in clinical trials, little is known regarding their effects on CRC. The aim of this study was to preclinically investigate the value of ABT-737 and Obatoclax as anticancer drugs for CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 47 publications
2
37
1
Order By: Relevance
“…1B), OBX was also found to cause cell cycle arrest (Fig. 1C), as described by Koehler et al in other colon cancer cell lines [45]; the fact that, at variance with the results of the present study, these Authors reported cell cycle arrest in G2/M rather than in G1 could depend on cell type-specific differences and/or on the Interestingly, while survival curves obtained for OBX under the three experimental conditions tested were totally superimposed in our preliminary experiments, the percentage of apoptotic cells induced by OBX increased significantly following hypoxic or chemical HIF-1α stabilization in HCT116 cells (Fig. 1B).…”
Section: Discussionsupporting
confidence: 84%
“…1B), OBX was also found to cause cell cycle arrest (Fig. 1C), as described by Koehler et al in other colon cancer cell lines [45]; the fact that, at variance with the results of the present study, these Authors reported cell cycle arrest in G2/M rather than in G1 could depend on cell type-specific differences and/or on the Interestingly, while survival curves obtained for OBX under the three experimental conditions tested were totally superimposed in our preliminary experiments, the percentage of apoptotic cells induced by OBX increased significantly following hypoxic or chemical HIF-1α stabilization in HCT116 cells (Fig. 1B).…”
Section: Discussionsupporting
confidence: 84%
“…This unique function, which goes beyond the antiapoptotic activity of full-length MCL-1 protein, makes MCL-1 indispensable for the survival of cancer cells (26,40). Furthermore, MCL-1 reportedly enhances the migratory and invasive potential of colorectal tumor cells, independently from its antiapoptotic effects (25,31). Consistently, we observed that improved ATP production, as well as enhanced migration and invasion of PHD3-deficient tumor cells, could be reverted by simultaneous knockdown of MCL-1.…”
Section: Discussionmentioning
confidence: 99%
“…The colorectal cancer cell lines HT29 and SW480 and the non-transformed colon cell line CCD 841 CoN were obtained from ATCC (Manassas, VA, USA) and cultured under standard conditions as described previously, supplemented with 10% fetal bovine serum (PAA laboratories, Cölbe, Germany) and 1% Penicillin/Streptomycin (Sigma-Aldrich, Munich, Germany) in a humidified atmosphere [45]. 5-Fluorouracil (5-FU) and Irinotecan were obtained from Sigma-Aldrich and dissolved in DMSO.…”
Section: Cell Lines and Chemotherapymentioning
confidence: 99%
“…Flow cytometry analyses were performed using a FACS CANTO II (Becton Dickinson, Franklin Lakes, NJ, USA) as described previously according to the protocol of Nicoletti et al [45]. Data were analyzed using the BD FACSDIVA ® software.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation